Heterogeneity of the diurnal cycle of precipitation in the Amazon Basin - Ramírez-Nina, Ronald G.; Silva Dias, Maria A. F. (Frontiers in Climate, 2024)
The diurnal cycle of precipitation in the Amazon Basin (AB) is not homogeneous, varying in its intensity, time of occurrence of precipitation peaks and in the shape of its diurnal distribution. This study presents a seasonal characterization of the mean diurnal cycle of precipitation in the AB from IMERG Final Run (∆x = 0.1° and ∆t = 30 min) database from 2001 to 2020. Diurnal and semi-diurnal oscillations were studied by harmonics analysis, i.e., using the first and second harmonics, respectively. Harmonic metrics of normalized amplitude (AN), phase and mean hourly precipitation rate were analyzed. The AN showed pixels within the AB with bimodal/uniform or unimodal distribution associated with the occurrence of two peaks (or none) or a single peak during the day. The phase of the first harmonic shows the time of occurrence of the precipitation rates peaks, as well as the displacement of the precipitation systems. The regionalization of the diurnal cycle was performed using the K-Means technique, showing that AB presents six clusters along its domain based mainly on the phase of the first harmonic. The spatial configuration of clusters showed seasonal variation, being modulated by the South American Monsoon System and the large-scale mechanisms responsible for triggering convection. However, their intensity, the shape of the diurnal distribution and the timing of precipitation peaks are modulated by local factors.